(untitled) (Research, Society and Development, 2022)
Third molars exhibit the greatest variability in developmental timing, crown and root morphology, and position. They are the last teeth to erupt into the oral cavity and complement the function of the second molars. The eruption or impaction of these teeth is an important consideration in treatment planning and long-term maintenance of the dentition, and therefore of particular interest to the orthodontist and dentist. Thus, the objective of this literature review is to describe the indications for the prophylactic removal of third molars, discussing the main advantages and disadvantages, as well as the possible complications related to the surgical procedure. For the construction of this work, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. There are clear indications for the removal of third molars associated with the pathology. However, asymptomatic erupted impacted third molars should be left alone and monitored regularly. Asymptomatic partially or fully erupted third molars should also be monitored periodically. When asymptomatic partially or fully erupted third molars exhibit periodontal pathology, such as pockets ≥ 4 mm, bleeding on probing, or attachment loss, a conservative approach involving periodontal maintenance is recommended. The clinician is also justified in deciding to extract the third molar(s) if oral hygiene is average and disease progression is likely.